Clinical Effectiveness of Mulligan’s Transverse Mobilization with Movement (MWM) in Improving Pain and Range of Motion in Subjects with Cervical Facet Dysfunction - MS.BHUVANESWARI.D; MR. SUBBIAH.K (International Journal of Pharma and Bio Sciences, 2018)
Facet or zygapophysial joint is considered to be common source of chronic spinal pain, and pain to adjacent structures, head, neck and shoulders. This chronic somatic segmental dysfunction involves fibrosis and thickening of zygapophysial joint capsule in the region of strain and this leads to range of motion restriction. Very limited evidences exist concerning the conservative and manual physical therapy management of cervical facet joint dysfunction. Currently few studies are found addressing lesion specific management that is directed towards facet dysfunction; hence the purpose of this study is to find out the effectiveness of Mulligan’s Transverse Mobilization with Movement (MWM) technique in improving pain and range of motion in subjects with cervical dysfunction. 44 subjects with cervical dysfunction were randomized into 2 groups. Subject in experimental group received transverse MWM, deep neck flexor training and subjects in control group received Range of motion (ROM) exercises, deep neck flexor training, both for 6 sessions. The subjects in experimental group had a statistically significant improvement on pain(df-0.99, P=0.005), ROM (df-flexion3.96degree; extension-8.77degree;right lateral flexion-7.50degree; left lateral flexion-5.45degree;right rotation-10.95degree; left rotation-10.27degree, 95%CI, P=0.215 for flexion & P=0..000 for other ranges) and functional outcomes(P=0.000) when compared to the control group. Transverse MWM when combined with exercises increases the likelihood of yielding better clinical outcome and can be considered as a lesion specific management for subjects with cervical dysfunction.